1995
DOI: 10.1016/0014-5793(95)00561-m
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Rhizobium meliloti in oxygen gradients

Abstract: Rhizobium meliloti cells responded to an abrupt protein [11]. The deoxy form of the FixL kinase is active and change in oxygen concentration by changing the cell speed transfers a phosphoryl group to the FixJ protein, a transcrip-(chemokinesis), but they did not alter the frequency at which tional activator of nitrogen fixation genes [9,12,13]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Even more interesting was the observation that the motility response observed for the different Shewanella strains correlated not only with the redox potential of the electron acceptors used in the different experiments, but also with the current-generating ability of the strains, again suggesting that this unique response could have a kinetic basis. We do note that the electrokinetic response is similar to the chemokinetic response observed by Zhulin et al (22), during studies on behavioral responses to oxygen in Rhizobium meliloti. These authors showed that R. meliloti responds to oxygen by increasing the swimming speed of cells and correlated this response with changes in proton motive force.…”
Section: Discussionsupporting
confidence: 56%
“…Even more interesting was the observation that the motility response observed for the different Shewanella strains correlated not only with the redox potential of the electron acceptors used in the different experiments, but also with the current-generating ability of the strains, again suggesting that this unique response could have a kinetic basis. We do note that the electrokinetic response is similar to the chemokinetic response observed by Zhulin et al (22), during studies on behavioral responses to oxygen in Rhizobium meliloti. These authors showed that R. meliloti responds to oxygen by increasing the swimming speed of cells and correlated this response with changes in proton motive force.…”
Section: Discussionsupporting
confidence: 56%
“…Our results show that highly motile bacteria can congregate at a preferred concentration gradient. This has been reported for aerotactic bacteria [10,14,32,33], but to the best of our knowledge has not been previously shown for amino acids. The formation of the motile bands by the marine bacteria could be a strategy evolved for life in a turbulent environment.…”
Section: Implications In the Open Oceansupporting
confidence: 44%
“…It is evident that the two cytoplasmic receptors are important for the chemokinesis response of S. meliloti ( (78). In addition, deleting either of the two PAS domain-encoding DNA regions had no effect on the chemotactic behavior of the resulting mutant strains on swarm plates (data not shown).…”
Section: Discussionmentioning
confidence: 95%